Dukungan Sosial Dengan Penerimaan Pada Orang Tua Yang Memiliki Anak Berkebutuhan Khusus (Social Support and Acceptance in Parents of Children with Special Needs) - Zaini, Arina Husna; 'Azizah, Nur (Program Studi Psikologi Islam (IAIN) Kediri, 2024)
Parents who are awarded a child with a diagnosis of special needs will feel sad and disappointed, the distrust they experience will give emotional reactions of anger, depression and bargaining in conditions that are not in accordance with their expectations. In these conditions dukungan sosial is needed to provide encouragement that is able to increase the acceptance of parents of children with special needs. The purpose of this study was to determine the relationship between dukungan sosial dan penerimaan for parents who have children with special needs. The sample in this study were 73 parents who have children with special needs in Tulungagung. The sampling technique used is simple purpoive sampling using dukungan sosial dan penerimaan as a measuring tool. The analysis technique uses non parametric statistics. Based on the results of the study, the significance correlation rank spearman obtained was 0.275, which means that there is no relationship between dukungan sosial dan penerimaan for parents who have children with special needs. However, this research has a positive correlation.